2016
DOI: 10.1016/j.apgeochem.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Emerging airborne contaminants in India: Platinum Group Elements from catalytic converters in motor vehicles

Abstract: Platinum Group Element (PGE) pollution on the Indian subcontinent is a growing concern because vehicle sales in India have rapidly increased over the last decade, and it is well known that automobile catalytic converters are one of the major source of anthropogenic PGE in the environment. Despite the rapid growth of the Indian automobile industry, the sources and magnitude of PGE contamination in Indian airborne particles are unknown. In this study we report PGE and mercury (Hg) concentrations, as well as osmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 61 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The XPS spectrum of the Pt 4f region for the Pt-sorbed AFMNC samples is also presented. Two peaks corresponding to the Pt 4f 7/2 and Pt 4f 5/2 transition were observed at binding energies of 74.7 and 78 eV, respectively, and correspond to PtCl 6 . This suggests that the dominant form of platinum species present on AFMNC surface is PtCl 6 2– . Along with this, a less intense peak at 72.6 eV was observed, which might be due to the partial reduction of Pt­(IV) ions to Pt­(II) on the AFMNC surface.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The XPS spectrum of the Pt 4f region for the Pt-sorbed AFMNC samples is also presented. Two peaks corresponding to the Pt 4f 7/2 and Pt 4f 5/2 transition were observed at binding energies of 74.7 and 78 eV, respectively, and correspond to PtCl 6 . This suggests that the dominant form of platinum species present on AFMNC surface is PtCl 6 2– . Along with this, a less intense peak at 72.6 eV was observed, which might be due to the partial reduction of Pt­(IV) ions to Pt­(II) on the AFMNC surface.…”
Section: Resultsmentioning
confidence: 96%
“…Due to its extensive usage, natural Pt resources are becoming depleted. However, demand for Pt is increasing steadily, and that trend is expected to continue. , Due to its usage in several fields, Pt concentrations in industrial effluents are increasing, leading to its accumulation in the environment. , This causes serious pollution in water, soil, and even in the air due to airborne Pt particles. …”
Section: Introductionmentioning
confidence: 99%
“…Determination of PGMs requires analytical methods of high sensitivity and selectivity, especially if they need to be quantified. Quantification most often relies on atomic absorption spectrometry (AAS) (17)(18)(19), atomic emission spectrometry (AES) (19,20), and mass spectrometry (MS) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Samples analysed by these methods must be in liquid state.…”
Section: Methods For Determining Pgms In Pmmentioning
confidence: 99%
“…Other authors have also reported using this preparation method to determine PGMs in particulate matter (21,29,30). Other authors (15,16,31), in turn, report using the NiS fire assay with isotope dilution. Rinkovec et al (28) report using high temperature and pressure microwave digestion system with acid digestion for PM 10 samples.…”
Section: Preparation Of Pm Samples Containing Pgmsmentioning
confidence: 99%
“…On average, approximately 3% of cardiopulmonary and 25% of lung cancer deaths are attributed to PM pollution globally. 11 In the megacities (populations of >10 million) of the IGB, such as Delhi and Kolkata, heavymetal-associated PM pollution is also an emerging major concern 12,13 because elevated concentrations of atmospheric PM were linked to increased morbidity and mortality rates in the region. 14,15 Monsoonal rainfall provides relief from PM pollution as ambient particles are removed from the atmosphere via several wet deposition processes.…”
Section: Introductionmentioning
confidence: 99%